Hak Regres Dalam Borgtocht: Telaah Terhadap Kepastian Hukum Bagi Penjamin Dalam Sistem Hukum Indonesia - R, Rafika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This journal aims to discuss the right of recourse (hak regres) within the legal framework of borgtocht (personal guarantee) under Indonesian civil law. Borgtocht is a form of personal guarantee whereby a guarantor is responsible for fulfilling a debtor’s obligation if the debtor fails to perform. Although the right of recourse is normatively regulated in Articles 1831 and 1839 of the Indonesian Civil Code, its implementation faces challenges, particularly in terms of technical execution, normative gaps, and weak legal protection. This normative legal research employs a descriptive approach to analyze statutory provisions, legal doctrines, and judicial precedents. The findings indicate the urgent need for implementing regulations that clearly define the recourse procedure, as well as strengthening contractual clauses that uphold the guarantor’s rights. Furthermore, consistent judicial decisions are essential to ensure legal certainty. Thus, the right of recourse must not only exist in theory but must also provide substantive protection for guarantors within a fair and balanced civil law system.